Isolation of new straight chain compounds from acacia nilotica - Chaubal, Rohini; Tambe, Amruta; Biswas, Sujata; Rojatkar, Supada; Deshpande, Vishnu; Deshpande, Nirinala (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2006)
A novel diester, pentacosane dioic acid dihexadecyl ester 1 has been isolated for the first time from n-hexane soxhlet extract of Acacia nilotica. Saponification of the diester reveals the presence of an alcohol, hexadecanol and pentacosane dioic acid. The structures of both the compounds are confirmed by GCMS analysis. Saponification of pet-ether extract of Acacia nilotica has been carried out. Unsaponiflable matter is further purified by column chromatography followed by repeated mixed solvent crystallization to afford heptacosan-1,2,3-triol 2.
Keywords: Acacia nilotica; diester; pentacosane dioic acid; saponification